Trans-Sulcal Parafascicular Port-Based Resection of a Subcortical Occipital High-Grade Glioma: 2-Dimensional Operative Video. Issue 1 (29th January 2022) - Revuelta Barbero, Juan M.; Rindler, Rima S.; Lamanna, Jason; Soriano, Roberto M.; Pradilla, Gustavo
Abstract : Minimally invasive trans-sulcal parafascicular port-based approaches can provide safe access to a wide variety of deep brain lesions. 1, 2 This surgical video illustrates the use of a minimally invasive port-based approach for resection of a subcortical right medial occipital lobe lesion in a 63-year-old woman who presented with seizures and bilateral left homonymous hemianopia. MRI showed a 2.5-cm contrast enhancing lesion with a necrotic center and significant T2 and fluid-attenuated inversion recovery signal consistent with vasogenic edema. Diffusion tensor imaging revealed compromise of the right optic radiations and edema extending through the right corticospinal tract. A minimally invasive trans-sulcal parafascicular port-based approach to the deep occipital lobe and periatrial region was performed under full exoscopic visualization. A gross total tumor resection was achieved, and histopathology revealed an IDH1-mutant, MGMT-methylated–positive glioblastoma. The patient's presentation, rationale, key surgical steps, and outcomes are discussed, and informed consent for surgery was obtained. The participants and any identifiable individuals consented to the publication of their image. Images at 3:50 used with permission from Nico Corporation. All rights reserved.